Synthesis and Spectroscopic and Biological Activities of Zn(II) Porphyrin with Oxygen Donors - Gauri Devi Bajju; Sujata Kundan; Madhulika Bhagat; Deepmala Gupta; Ashu Kapahi; Geeta Devi (Bioinorganic Chemistry and Applications)
Results of investigation of the physicochemical properties of zinc complexes containing substituted phenols as axial ligand having general formula [X-Zn-t(p-CH3) PP] [where X = different phenolates as axial ligand] in impurity-free organic solvent are presented. The four-coordinated zinc porphyrin accepts one axial ligand in 1 : 1 molar ratio to form five-coordinated complex, which is purified by column chromatography and characterized by physicochemical, biological evaluation and TGA/DTA studies. Absorption spectra show two principal effects: a red shift for phenols bearing substituted electron releasing groups (−CH3, −NH2) and blue shift for phenols bearing electron withdrawing groups (−NO2, −Cl) relative to Zn-t(p-CH3) PP, respectively. 1H NMR spectra show that the protons of the phenol ring axially attached to the central metal ion are merged with the protons of the porphyrin ring. Fluorescence spectra show two fluorescence peaks in the red region with emission ranging from 550 nm to 700 nm. IR spectra confirm the appearance of Zn-NPor and Zn-O vibrational frequencies, respectively. According to the thermal studies, the complexes have a higher thermal stability and the decomposition temperature of these complexes depends on the axial ligation. The respective complexes of X-ZnII-t(p-CH3) PP were found to possess higher antifungal activity (up to 90%) and higher in vitro cytotoxicity against human cancer cells lines.